Challenges of Integrating Mobile Technology into Mathematics Instruction in Secondary Schools: An Indonesian Context. Issue 3 (3rd July 2017) - Abidin, Zaenal; Mathrani, Anuradha; Hunter, Roberta; Parsons, David
ABSTRACT: Implementing mobile learning in curriculum-based educational settings faces challenges related to perceived ethical and learning issues. This study investigated the affordances of mobile technologies to support mathematics instruction by teachers. An exploratory study employing questionnaires and semi-structured interviews revealed that, while mathematics instruction can be augmented with mobile learning, the majority of schools in Indonesia have banned student use of mobile phones in classrooms. Teachers are concerned about the improper use of mobile phones that could impact their students' mental well-being and distract them from learning. Most teachers perceive mobile technologies to be disruptive and seem reluctant to use them for teaching delivery. However, teachers are eager to experiment with digital technologies within mathematics instruction. Our findings suggest infusing alternate technologies that fit better with the school's teaching and learning environment. This includes web-based applications that can run on different digital devices ranging from desktop computers, laptops, and tablets, to mobile phones. We propose setting up communities of practice for mathematics teachers to share their instructional repertoire on integrating digital technologies within the classroom.